The breakdown of the Simon effect in cross‐modal contexts: EEG evidence. (2nd April 2018) - Castro, Leonor; Soto‐Faraco, Salvador; Morís Fernández, Luis; Ruzzoli, Manuela
Abstract: In everyday life, we often must coordinate information across spatial locations and different senses for action. It is well known, for example, that reactions are faster when an imperative stimulus and its required response are congruent than when they are not, even if stimulus location itself is completely irrelevant for the task (the so‐called Simon effect). However, because these effects have been frequently investigated in single‐modality scenarios, the consequences of spatial congruence when more than one sensory modality is at play are less well known. Interestingly, at a behavioral level, the visual Simon effect vanishes in mixed (visual and tactile) modality scenarios, suggesting that irrelevant spatial information ceases to exert influence on vision. To shed some light on this surprising result, here we address the expression of irrelevant spatial information in EEG markers typical of the visual Simon effect (P300, theta power modulation, LRP) in mixed‐modality contexts. Our results show no evidence for the visual‐spatial information to affect performance at behavioral and neurophysiological levels. The absence of evidence of the neural markers of visual S‐R conflict in the mixed‐modality scenario implies that some aspects of spatial representations that are strongly expressed in single‐modality scenarios might be bypassed. Abstract : By means of a mixed‐modality Simon task in an EEG protocol, we have showed that irrelevant spatial information in vision, which classically exerts a strong effect on responses, fails to affect performance at the behavioral level as well as to produce neurophysiological evidence of spatial interference. We suggest that in a task in which a spatial representation is pivotal, the relevant reference frame is built up involuntarily (as previous hypotheses suggest) but rather more flexibly than previously thought, as a function of the context and task demands.